Revisiting the Antecedents of Green Marketing Communication: A Pathway towards Sustainability - Singla, Kavita; Thakur, Anand; Kohli, Simriti (Gyan Management Journal, 2023)
Companies these days, are recognizing the relevance of pro environmental marketing strategies in their business practices. But prevailing malpractices of greenwashing have increased consumers’ scepticism about companies’ green endeavours. Need of the hour is to effectively communicate genuine sustainable practices to eradicate brand mistrust and promote ecological behaviour among consumers.Literature Review Though some efforts have been made in strengthening the literature on GMC by Chang et al. (2021), Koo et al. (2006), Dinh et al. (2023), Mao & Zhang (2013). But the integrated framework on the same is still unavailable. Purpose of the Study The present study aims to propose a theoretical framework conceptualizing the antecedents of Green Marketing Communication that shape the consumers’ attitude towards GMC. Research Methodology Based on the exploratory qualitative design, the study proposes and corroborates various antecedents of GMC drawn from previous literature.